Destination leadership: A new paradigm for tourist destinations? - Pechlaner, Harald; Kozak, M.; Volgger, M. (Emerald Group Publishing Limited, 2014)
This special issue of Tourism Review provides an original body of work that complements existing research on tourist destinations, and offers an opportunity for tourism research to contribute to broader leadership theorizing. This editorial introduction embeds the included papers into general reflections about destination leadership. This introduction summarizes how the papers in this special issue contribute to two streams of research: First, the papers use and advance leadership theories that are particularly suited to inter-organizational contexts, such as distributed and systemic leadership. Second, they illustrate that destination leadership needs to be treated and understood in relationship to governance arrangements, power structures, and social networks among leaders. Sustainable destination competitiveness greatly depends on effective strategies as well as efficient and inclusive processes and structures. Existing research on destination management and destination governance clearly illustrates the relevance of these requirements. However, the human factor in the form of motivation, inspiration, and role modeling – i.e. destination leadership – is also crucial. Yet, so far leadership has not received the necessary attention in both tourist destinations and networked environments in general. This is all the more remarkable since social networks pose particular challenges for leadership.